MANAGEMENT DECISION-MAKING IN THE TRANSFORMATION OF HIGHER EDUCATION - M. Bolgova; E. Evdokimova (Вестник университета)
The main directions of the transformation of higher education in the Russian Federation. Clarifications on the role of leadership in the management decision-making in higher education. The formation of a broad group of larger competitive at the national level, regional universities and their focus on quality training of specialists in demand on the regional labor market. Obtained problem management decision-making, strategy development and their relationship with the state policy in the sphere of higher education.